1988
DOI: 10.1159/000125002
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Intermittent Release of Gonadotropin-Releasing Hormone in the Prepubertal Male Rhesus Monkey Induced by N-Methyl-DL-Aspartic Acid

Abstract: The purpose of the present study was to determine whether gonadotropin-releasing hormone (GnRH) neurons in the hypothalamus of the prepubertal monkey may be prematurely provoked into producing a sustained train of intermittent GnRH release. N-methyl-DL-aspartic acid (NMA), an analog of the putative excitatory neurotransmitter aspartate, was used to stimulate the hypothalamus. In order to utilize pituitary luteinizing hormone (LH) secretion as a bioassay of hypothalamic GnRH release, juvenile males were castrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(34 citation statements)
references
References 14 publications
0
32
1
1
Order By: Relevance
“…injections of an NMDA receptor agonist elicited a sustained train of hypothalamic GnRH discharges at this stage of development (23). In striking contrast to GnRH release, GnRH gene expression and GnRH peptide content in the hypothalamus are maintained during juvenile development in the monkey (24,25).…”
Section: Discussionmentioning
confidence: 98%
“…injections of an NMDA receptor agonist elicited a sustained train of hypothalamic GnRH discharges at this stage of development (23). In striking contrast to GnRH release, GnRH gene expression and GnRH peptide content in the hypothalamus are maintained during juvenile development in the monkey (24,25).…”
Section: Discussionmentioning
confidence: 98%
“…In the rhesus monkey (Macaca mulatta), the responsiveness of pituitary gonadotropes to GnRH stimulation is clearly enhanced by a preceding chronic pulsatile infusion of GnRH [63]. This important observation led Plant and colleagues [64,65,66,67,68]to employ a standard GnRH priming protocol in their studies where gonadotropin secretion is measured in response to various factors. Studies have also been conducted in men exhibiting gonadotropin deficiency, and in the absence of any pituitary defects it has been reported that GnRH priming improves gonadotropin secretion [69,70].…”
Section: Kiss1r Displays Basal Constitutive Signaling and Kp-independmentioning
confidence: 99%
“…That reaugmentation of pulsatile GnRH release at the time of puberty is unrelated to any maturational changes of the GnRH neurons themselves is suggested by the findings that the hypothalamic contents of immunoactive GnRH, bioactive GnRH and the messenger RNA (mRNA) coding for the decapeptide in prepubertal monkeys are similar to those in adults [2, 3, 4]. Moreover, repetitive hourly stimulation of the GnRH neuronal system of juvenile monkeys by N-methyl- D -aspartate, a glutamate receptor agonist, results in the immediate activation of an adult-like pattern of pulsatile GnRH release [5, 6]. The latter result suggests that initiation of the pubertal enhancement of pulsatile GnRH release in primates is determined by developmental changes in an ‘upstream’ input to the neurons responsible for the secretion of this hypophysiotropic factor.…”
Section: Introductionmentioning
confidence: 99%